ANALISIS GENDER DALAM KEHIDUPAN KELUARGA PEMBUDIDAYA RUMPUT LAUT (EUCHEUMA SP) DI KELURAHAN PANTAI AMAL KECAMATAN TARAKAN TIMUR - Nurlina -; Dayang Diah Fidhiani; Qoriah Saleha (Jurnal Pembangunan Perikanan dan Agribisnis, 2020)
The purpose of this research is to examine how people's perceptions to gender roles in families, to describe the division of labor in productive, reproductive, and social activities, to examine how the opportunities of access and control that men and women, to examine how the opportunities of decision-making that men and women have in the seaweed cultivation business. The sample in this research amounted to 30 families of seaweed cultivators with the criteria of a married couple using a qualitative approach, which was obtained by interview using a questionnaire and direct observation data which obtained by analyzed descriptively. The result of this research indicate that: (1) Perceptions of gender that are most highly held by both men and women are "men and women realize that gender differences do not have to be opposed in living a family, but rather be mutually supportive and complementary". (2) The division of labor regarding to the activities of productive is more dominantly done by men while the activities of reproductive are more dominantly done by women. (3) Access in terms of family resources can be accessed by men and women, while in control pattern it spreads between men and women. (4) Decision-making in activities of productive is more dominated by men, but in the social sector decision-making patterns are made together between men and women. Whereas the predominant activities of reproductive are carried out together. Keyword : Gender, division of work, Access and Control, Decision making, Seaweed, Pantai Amal